E-Governance, Administrative Hurdles, and Online Income Tax Compliance Among Nepalese Firms - Adhikari, Shankar (Nepalese Journal of Management and Technology, 2025)
The Government of Nepal has implemented several e-governance initiatives to modernize tax administration, including online income tax filing, electronic payment systems, and Permanent Account Number (PAN) services through the Inland Revenue Department (IRD). Despite these efforts, Nepalese firms continue to experience significant challenges in tax compliance due to technological limitations, organizational constraints, and persistent administrative hurdles. This study investigates the combined influence of e-governance factors and administrative barriers on online income tax compliance behavior among Nepalese firms. Grounded in the Technology Acceptance Model (TAM) and administrative burden theory, the study examines key determinants such as ease of use, perceived usefulness, IT infrastructure readiness, management support, security and privacy concerns, and administrative obstacles. Firm size and industry type are incorporated as moderating variables to better understand contextual variations. A quantitative, cross-sectional research design was adopted, with data collected from 286 respondents across diverse sectors. Analytical methods include descriptive statistics, correlation, regression, moderation analysis, and confirmatory factor analysis (CFA), providing insights and policy recommendations for improving digital tax governance.